Outcome of pigs with short gut syndrome submitted to orthotopic intestinal transplantation - Llanos, Juan Carlos [UNESP]; Ruiz, Philip; Takahashi, Hidenori; Delacruz, Victor; Bakonyi Neto, Alexandre [UNESP] (Acta Cirurgica Brasileira, 2015)
Purpose: to evaluate the current model of small bowel resection and intestinal transplantation in pigs. Methods: forty two large white pigs were distributed in five groups: g1(n=6), g2(n=6) and g3(n=6) were submitted to 80%,100% and 100% plus right colon resection respectively and g4(n=7) and g5(n=5) to 100% sbr plus it without and with immunosuppression based on tacrolimus and mycophenolic acid. evaluation included weight control, clinical status, biochemical analysis and endoscopies for graft biopsies. Follow-up in g1 and 2 was 84 days, while in g3, four and five was ± three weeks. Results: g1 increased weight suggesting adaptation while g2 and 3 loused weight and inadequate adaptation. g4 and 5 died of acute cellular rejection (acr) and sepses respectively. overall survival in g1, 2, 3, 4 and 5 at 30 days was 100, 100, 0 and 20 %, respectively. medium survival in g4 and 5 was 14 and 16 days. Conclusions: the resection of 80% of small intestine in pigs is not suitable for short bowel syndrome induction. intestinal transplantation with the proposed immunosuppression protocol was effective in prevent the occurrence of severe acute rejection, but inappropriate to increase recipients survival.
Keywords: Transplantation; Short Bowel Syndrome; Graft Rejection; Swine